An electric-field-dependent drop selector. Issue 7 (8th March 2019) - Yang, Jinlong; Wang, Dehui; Liu, Hailong; Li, Linxian; Chen, Longquan; Jiang, Hong-Ren; Deng, Xu
Abstract : We have designed a superhydrophobic-coated chip to manipulate the static and dynamic behaviors of a drop using dielectrowetting. Abstract : Drop manipulation on hydrophobic surfaces is of importance in lab-on-a-chip applications. Recently, superhydrophobic surface-assisted lab-on-a-chips have attracted significant attention from researchers due to their advantages of contamination resistance and low adhesion between the drop and the surface during manipulation. However, control over both static and dynamic interactions between a drop and a superhydrophobic surface has been rarely achieved. In this study, we designed an electric-field-dependent liquid-dielectrophoresis force to manipulate a drop on a superhydrophobic surface. This type of control has been found to be fast in response, bio-friendly, convenient, repeatable, and energy efficient. Moreover, the adhesion force and rebounding for both the static and the dynamic interactions between the drop and the surface under an electric field have been explored. It was found that the adhesion force could be reversibly tuned three-fold without breaking the Cassie–Baxter state. Rebounding experiments showed a close to linear relation between energy dissipation and the applied voltage. This relation was used to tune the on-demand behaviors of a drop on a surface in a proof-of-concept experiment for drop sorting. This electric-field-dependent drop manipulation may have potential applications in digital microfluidics, micro-reactors and advanced lab-on-a-drop platforms.